Configuration design method of hybrid electric agricultural machinery system based on layered two-dimensional matrix - Li, Baogang; Pan, Jinbo; Sun, Rui; Li, Yuhuan; Liu, Zunmin; Huang, Wanyou; Jiang, Hanjun; Liu, Fuhao (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The working environment and objects of agricultural machinery are different from those of automobiles, and agricultural machinery is greatly affected by such working environment and working conditions, while its power output system is more complex. Agricultural machinery not only has drive output, but also PTO output and hydraulic output, which together constitute the output system of agricultural machinery. Agricultural machinery conditions can be divided into road transportation working conditions and field operation working conditions. The working conditions of agricultural machinery can be divided into different load conditions according to the different traction tools and whether the hydraulic and PTO work, such as ploughing, rotary tillage, fertilization and transportation. Therefore, developing hybrid electric agricultural machinery systems that are suitable for various complex working conditions holds great theoretical significance and practical value. This should be done bearing mind the complex working conditions of agricultural machinery systems in agricultural work and the intricate challenges in designing hybrid agricultural machinery systems. In this paper, a two-dimensional matrix is used to represent the physical structure and dynamics of the multi-channel power output agricultural mechanism. A hierarchical two-dimensional matrix method for the generation and screening of hybrid electric agricultural machinery systems with multi-power output power is also proposed. The components of agricultural machinery are divided into an input layer and an output layer, and these components are coded and defined, and then transformed into a matrix. The hierarchical two-dimensional matrix method is used to generate and screen the hybrid electric agricultural mechanism type. Through the stratification of the matrix, complexity of the configuration generation is reduced, and the constraints are applied to the basic screening of the configurations generated. The rationality of the configurations obtained after generation and screening is verified by Simulink simulation. The results show that the configuration screened by this method can meet the performance requirements of agricultural machinery.